2022
DOI: 10.1371/journal.pone.0262951
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on wheat and maize growth in Ethiopia: A multi-model uncertainty analysis

Abstract: Ethiopia’s economy is dominated by agriculture which is mainly rain-fed and subsistence. Climate change is expected to have an adverse impact particularly on crop production. Previous studies have shown large discrepancies in the magnitude and sometimes in the direction of the impact on crop production. We assessed the impact of climate change on growth and yield of maize and wheat in Ethiopia using a multi-crop model ensemble. The multi-model ensemble (n = 48) was set up using the agroecosystem modelling fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…61%, 0.92, 0.85 and 1.41 days, 1.31%, 0.99 and 0.91, respectively (Table3). Similarly, a close agreement was observed between the simulated and observed anthesis and maturity dates(Araya et al 2019;Rettie et al 2022). The model simulated anthesis and maturity dates with RMSE and nRMSE lower than 2 and d values greater than 0.85, respectively, for wheat in Ethiopia.…”
supporting
confidence: 75%
“…61%, 0.92, 0.85 and 1.41 days, 1.31%, 0.99 and 0.91, respectively (Table3). Similarly, a close agreement was observed between the simulated and observed anthesis and maturity dates(Araya et al 2019;Rettie et al 2022). The model simulated anthesis and maturity dates with RMSE and nRMSE lower than 2 and d values greater than 0.85, respectively, for wheat in Ethiopia.…”
supporting
confidence: 75%
“…The decadal trend finding suggested that tef and barley yields were growing, whereas wheat and faba bean yields were dropping in Farta district (Figure 12). Climate variable both negative and positive relationships with crop yields reported by many scholars (Abera et al, 2018; Alaminie et al, 2021; Ginbo, 2022; Rettie et al, 2022; Wakjira et al, 2021). The result revealed that there was a nonsignificant negligible negative and weak positive correlation between tef yield with the annual rainfall (−0.229) and minimum temperature (0.348), respectively, in Yilmana Densa district (Table 9).…”
Section: Resultsmentioning
confidence: 88%
“…Changes in land and water regimes will have an effect on agricultural productivity as a result of the changing consensus of climate elements such as temperature and precipitation. The agricultural dependency GDP and low adaptive capacity of the African countries' climate change are severely affecting them (FEWS NET, 2022;Mahrous, 2019;Samuel et al, 2021;Thomas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on economic theories on food demand and supply gap, which posit a greater demand on food commodities against low supplies, calls for immediate actions and policies to sustain food production and security in the state are increasingly relevant. However, this study differs from previous studies on cereal crops such as rice, wheat, maize, sorghum, and tuber crops such as cassava, yam, cocoyam, (Boansi, 2017;Wang et al 2018;Asfew &Bedemo, 2022;Rettie et al, 2022;Mariem et al, 2021) because it focuses on sweet potatoes. Sweet potatoes are one of Nigeria's under-exploited and forgotten food crops which contributes significantly to Nigeria's gross domestic product, as the country is the major producer in Africa and second largest producer in the world.…”
Section: Introductionmentioning
confidence: 73%